A mathematical model and tabu search algorithm for multi-manned assembly line balancing problems with assignment restrictions. Issue 5 (3rd May 2020) - Yilmaz, Hamid; Yilmaz, Mustafa
ABSTRACT: A multi-manned assembly line is a set of workstations where task operations can be performed on multiple sides of the line. Such assembly lines are important for large products, such as buses, cars and trucks. In this study, a mathematical model for multi-manned assembly lines with assignment restrictions is proposed. The purpose of the mathematical model is to minimize the total number of workers and open multi-manned workstations along the line for a given cycle time simultaneously under various assignment restrictions. The model provides a more realistic situation for multi-manned assembly line problems. The tabu search algorithm (TSA) is also used to solve the problem. The performances of both methods on well-known data-set problems are analysed. Based on the computational experiments, the performance of the proposed TSA is compared with the mathematical model solutions on various problem instances. The experimental results verify the effectiveness and efficiency of the proposed TSA.